2014
DOI: 10.1016/s2213-8587(13)70199-2
|View full text |Cite
|
Sign up to set email alerts
|

Fructosamine and glycated albumin for risk stratification and prediction of incident diabetes and microvascular complications: a prospective cohort analysis of the Atherosclerosis Risk in Communities (ARIC) study

Abstract: Background Hemoglobin A1c (HbA1c) is the standard measure to monitor long-term glucose control in diabetes management and is now used for diagnosis. Fructosamine and glycated albumin are markers of short-term glycemic control that may add complementary information to HbA1c. However, the performance of fructosamine and glycated albumin to identify people at risk of complications is unclear. Methods We measured glycated albumin and fructosamine in 11348 adults without diabetes and 958 adults with diagnosed dia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

7
185
0
5

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 224 publications
(197 citation statements)
references
References 35 publications
7
185
0
5
Order By: Relevance
“…The G-gap is also reported to be an indicator with biological variation [5,31], and Nayak et al [6] reported that the G-gap has consistent biological variability in individuals. Recently, as mentioned above, fructosamine or GA and G-gap have been reported as predictive indicators for diabetic complications independent of A1C [16,17,32]. If the GA/A1C-SI ratio reflected the difference in biological variability of glycation between GA in the circulation and A1C within the cell, the GA/ A1C-SI ratio might be a predictive indicator of diabetic complications accurately representing the G-gap.…”
Section: Discussionmentioning
confidence: 91%
See 3 more Smart Citations
“…The G-gap is also reported to be an indicator with biological variation [5,31], and Nayak et al [6] reported that the G-gap has consistent biological variability in individuals. Recently, as mentioned above, fructosamine or GA and G-gap have been reported as predictive indicators for diabetic complications independent of A1C [16,17,32]. If the GA/A1C-SI ratio reflected the difference in biological variability of glycation between GA in the circulation and A1C within the cell, the GA/ A1C-SI ratio might be a predictive indicator of diabetic complications accurately representing the G-gap.…”
Section: Discussionmentioning
confidence: 91%
“…GA is not affected by other glycated proteins in serum, compared with fructosamine which is including glycated proteins other than albumin. Selvin et al reported the prediction of incident diabetes and microvascular complications by both fructosamine and GA [17]. Thus, GA is considered to be almost biologically equal to fructosamine for calculating G-gap.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Similarly, higher levels of plasma lactate are associated with incident T2DM (31) and could modify calcium fractions (28). Lastly, it is worth noting that adjustment for albumin concentration has been proposed for another biomarker associated with incident T2DM (fructosamine) (32,33), although it is still unclear the appropriateness of such adjustment given (34). Interestingly, our results are in line with a previous study showing no difference in direct iCa measurement comparing subjects with and without diabetes (11); notably, the Authors speculated that 'correction' of total calcium for serum albumin would not be appropriate because of an increased serum free fatty acids concentrations.…”
Section: Discussionmentioning
confidence: 99%